Organizational Evaluation of the Benefits, Constraints and Satisfaction with Business-To-Business Electronic Commerce - Standing, C.; Lin, Chad (M.E. Sharpe, Inc., 2007)
Organizations that wish to be competitive must engage successfully in business-to-business (B2B) electronic commerce, but there has been little research on how organizations evaluate their B2B e-commerce investments, the extent to which they benefit from their investments, and how these factors relate to their satisfaction with B2B e-commerce systems. A multi-case approach is used to determine where and how organizations evaluate their B2B e-commerce initiatives. The relationships between constraints, evaluation practices, benefits, and satisfaction with B2B e-commerce investments are explored. The results show that (1) the level of constraint affects the degree of evaluation undertaken and the use of evaluation methodologies, (2) the use of evaluation methodologies affects the level of benefits obtained from B2B e-commerce, and (3) organizations that use evaluation methodologies are more satisfied with their B2B e-commerce. A B2B e-commerce evaluation-satisfaction model is developed that can enable organizations to adopt and effectively use evaluation methodologies in order to enter a cycle of continuous B2B e-commerce improvement that will result in high levels of satisfaction with their systems.